1993
DOI: 10.2214/ajr.161.5.8273605
|View full text |Cite
|
Sign up to set email alerts
|

The corpus callosum: normal fetal development as shown by transvaginal sonography.

Abstract: Ion (58100) OBJECTIVE.Detection of the corpus callosum in the developing fetus on sonograms usually is difficult. We determined the normal appearance and development of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 2 publications
8
139
3
1
Order By: Relevance
“…At prenatal ultrasound a fully developed corpus callosum is seen to overlay the quadrigeminal plate of the mesencephalon in the median view of the fetal brain. However, when dealing with the suspicion of callosal underdevelopment, either partial agenesis or hypoplasia, normative charts of its length and thickness are available for comparison 13,14 . If these biometric parameters are below the normal range an objective diagnosis of callosal underdevelopment may be established prenatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At prenatal ultrasound a fully developed corpus callosum is seen to overlay the quadrigeminal plate of the mesencephalon in the median view of the fetal brain. However, when dealing with the suspicion of callosal underdevelopment, either partial agenesis or hypoplasia, normative charts of its length and thickness are available for comparison 13,14 . If these biometric parameters are below the normal range an objective diagnosis of callosal underdevelopment may be established prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of callosal hypoplasia or partial agenesis ultrasound diagnosis is based, respectively, on the demonstration of a decreased thickness of the corpus callosum or a decreased thickness and abnormal shape, in the median view. Normative charts for fetal corpus callosal biometry have been established and are of critical importance in assisting the sonographer during subjective assessment to confirm either corpus callosal integrity or its underdevelopment 13,14 . Prognostic implications for fetuses with partial agenesis seem to be similar to those for fetuses with total agenesis 1,7,15 , although some claim there to be a better outcome in the former group 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Such anomalies can be subtle leading to difficulties in prenatal diagnosis and management. In addition, secondary disruption of SP due to severe hydrocephaly has been reported (Malinger et al, 1993). When associated with optic nerve hypoplasia, ASP is a classical feature of SOD.…”
Section: Absent Septum Pellucidum and Septo-optic Dysplasiamentioning
confidence: 99%
“…In fetuses in vertex presentation the transvaginal approach is preferred (Monteagudo et al, 1991;Malinger et al, 1993); in breech presentation a transfundal approach is suggested. Recently, the use of 3D multiplanar technique has also been proposed (Pilu et al, 2006) (Figure 3), as it offers a more accurate identification of the mid-sagittal plane, whereas navigation in the other two simultaneous orthogonal planes may permit a better evaluation of the midline prosencephalic structures.…”
Section: Sonographic Findingsmentioning
confidence: 99%
“…As the CC is part of the highest order, latest maturing mental network of the brain, its measurements are important to assess normal brain development and to locate structural changes that may disturb cognitive skill development. Although prenatal detection of CC abnormalities has been widely reported [6][7][8][9] its normal in utero growth and development are scarcely documented 10,11 . Until quite recently, direct in utero evaluation of the human fetal CC was not possible 12 .…”
Section: Introductionmentioning
confidence: 99%